Dinamika sosial masyarakat Abbasiyyah: Kajian sosiologi historis - Darajati, Aflaha Putri (Maliki Interdisciplinary Journal, 2024)
There have been various social phenomena which are a form of deviation from Islamic teachings. Regardless of the name of the Abbasid period as the heyday of Islam, who would have thought that such deviations occurred. However, this actually happened unconsciously if we look at the passage of time that led to the deviation occurring. A hatred of tribal opponents in Abbasid society was the first step of deviation and ended in the collapse of the Abbasid dynasty. By studying Auguste Comte’s historical sociology using literature analysis, all the causes of social phenomena that occurred at that time can be revealed. A truth cannot be concluded absolutely even in a government that has an Islamic nuance. Because all mistakes can happen, and cannot be avoided. By looking favorably at the Abbasiyyah government as it is labeled "the glory days of Islam" of course it will not be separated from the various bad traits that dominate its society, causing conflict and bad traditions as revealed by the History of the Abbasiyyah period in the book Al ’Abbas by Syauqi Dhoif.